Fatty acid esters as novel metabolites of γ‐hydroxybutyric acid: A preliminary investigation. Issue 4 (11th January 2022) - Kraemer, Michael; Broecker, Sebastian; Kueting, Theresa; Madea, Burkhard; Maas, Alexandra
Abstract: γ‐Hydroxybutyric acid (GHB) is a substance frequently abused as a knockout agent. Because of possible amnesia experienced by victims of GHB exposure and the short detection time of GHB in biological samples, the proof of GHB uptake is often challenging for forensic toxicologists. For this reason, various approaches have been evaluated to prolong the detection of GHB intake. In the present study, a fatty acid ester of GHB (4‐palmitoyloxy butyrate [GHB‐Pal; 3‐carboxypropyl hexadecanoate]) was synthesized with the intent of examining whether such esters could be detected as metabolites of GHB in blood samples. Using the structurally elucidated synthesis product (structural elucidation by means of high performance liquid chromatography quadrupole time of flight mass spectrometry [LC‐QToF‐MS]), an LC triple quadrupole mass spectrometric (LC–MS/MS) method was established for the detection of GHB‐Pal. Blood (plasma) samples from four cases in which GHB was previously detected at relevant concentrations (56.1–96.5 μg/ml) were analyzed with respect to GHB‐Pal. Signals for GHB‐Pal, as well as possible signals for other fatty acid esters of GHB, were detectable in these specimens. (Negative) control samples (20 plasma samples and 20 red blood cell/blood clot samples; from cases in which an intake of GHB or its precursors was not assumed) were all negative for GHB‐Pal. To evaluate a possible forensic benefit of GHB fatty acid esters (prolongation of the detection window of a GHB uptake), the analysis of additional plasma samples collected after GHB uptake (or controlled GHB administration) and quantification of GHB fatty acid esters are needed. Abstract : The occurrence of fatty acid esters as novel metabolites of γ‐hydroxybutyric acid (GHB) in blood samples was investigated using a self‐synthesized ester (3‐carboxypropyl hexadecanoate, GHB‐Pal). Signals of GHB‐Pal were detectable in blood plasma samples in which GHB was previously detected at relevant concentrations. To evaluate a possible forensic benefit of GHB fatty acid esters, further investigations are required.